Structure and dynamics of benzyl-NX3 (X = Me, Et) trifluoromethanesulfonate ionic liquids - Sunda, Anurag Prakash; Dhavale, Vishal M.; Kurungot, Sreekumar; Venkatnathan, Arun (Journal of Physical Chemistry B, 2014)
Ammonium-based benzyl-NX3 (X = methyl, ethyl) trifluoromethanesulfonate (TFA) ionic liquids (ILs) are low cost, nontoxic, thermally stable ion-conducting electrolytes in fuel cells and batteries. In the present study, we have characterized the structure and dynamics of these ILs using molecular dynamics (MD) simulations and ionic conductivity using electro-chemical impedance spectroscopy (EIS) at varying temperature and relative humidity (RH). Results from MD simulations predict that cation-cation and cation-anion interactions are stronger in benzyltrimethylammonium (BzTMA) compared to benzyltriethylammonium (BzTEA) that diminish with increase in RH. Further, the BzTMA cations show both C-H/Ph (center of mass of phenyl ring) and cation-Ph interactions whereas BzTEA cations show only strong cation-Ph interactions. The C-H/Ph interactions (psi >= 90 degrees, d(H-Ph) <= 4 angstrom, theta < 50 degrees and d(C.Ph) <= 4.3 angstrom) in BzTMA cations increase with RH and are highest at RH = 90%. The cumulative impact of electrostatic, cation/Ph, and C-H/Ph interactions results in lower conductivity of BzTMA-TFA IL compared to BzTEA-TFA IL. The EIS measurements show that the trends in ionic conductivity of ILs at RH = 30 and 90% are qualitatively similar to the Nernst-Einstein conductivity from MD simulations. The ionic conductivity of BzTEA-TFA IL is similar to 3 times higher than BzTMA-TFA IL at 353 K and RH = 90%.